Comparative Analysis of Microstructure and Physicochemical Properties of Sweetpotato (Ipomoea batatas (L.) Lam) Starch - Chen MA; Yongyue ZHANG; Jian SUN; Ruixue YUE; Yi ZHANG; Hong ZHU; Wenting ZHANG; Shaoying DENG (Shipin gongye ke-ji)
To explore and make use of the properties of sweetpotato starch (Luoshu), the particle morphology, particle size, ordered structure, lamella structure, amylose content, amylopectin chain length distribution, degree of branching, thermal, pasting and rheological properties of sweetpotato starch were analyzed. Furthermore, the correlations between their microstructure and physicochemical properties were also studied using correlation analysis. The starch granules were round spherical, round-like, oval, hemispherical, and angled polyhedral shapes, and the median diameter range was 15.01~18.40 μm. The pasting pattern of the sweetpotato starch was "from the central umbilical point of the starch granule to the surface", and the main fragments of amylopectin were short chains, with fa and fb1 chains accounting for 76.27%~79.22%. Luoshu 9 and Luoshu 10 had high peak viscosity and swelling power. Luoshu 11 had low breakdown value, high storage modulus and loss modulus. Luoshu 12 exhibited the lowest setback value and was difficult to retrogradation. Luoshu 14 had good thermal stability and elasticity. Luoshu 16 had the highest amylose content and setback value. Therefore, Luoshu 9 and Luoshu 10 could be used as thickeners, Luoshu 11 was suitable for baked foods, Luoshu 12 was suitable for frozen products, Luoshu 14 could be used as raw materials for jelly, and Luoshu 16 was suitable for starch noodle processing. In addition, particle size, molecular structure of amylose and amylopectin, short-range order degree were the key factors affecting the thermal stability, pasting and gel properties of sweetpotato starch. A significant correlation was observed between the microstructure and physicochemical properties of starch made from different varieties of sweetpotatoes, thus providing a basis for the processing and utilization of sweetpotato starch as well as sweetpotato breeding.